2022
DOI: 10.3390/toxics10100549
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Risk Meets Inter-Individual Variability: Probabilistic Concentration Addition of Complex Mixture Exposures in a Population-Based Human In Vitro Model

Abstract: Although humans are continuously exposed to complex chemical mixtures in the environment, it has been extremely challenging to investigate the resulting cumulative risks and impacts. Recent studies proposed the use of “new approach methods,” in particular in vitro assays, for hazard and dose–response evaluation of mixtures. We previously found, using five human cell-based assays, that concentration addition (CA), the usual default approach to calculate cumulative risk, is mostly accurate to within an order of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…NAMs have been applied to assess additional factors that contribute to variability and susceptibility such as sex [16,17], life stage [16,18,19], and comorbidities [20], including rare diseases [21]. Moreover, NAMs have the potential to incorporate complex mixtures and cumulative exposures [22][23][24]. Probabilistic methods can incorporate variability into predictions and have been used to derive reference dose estimates [25] and points of departure [23].…”
Section: Genomicsmentioning
confidence: 99%
“…NAMs have been applied to assess additional factors that contribute to variability and susceptibility such as sex [16,17], life stage [16,18,19], and comorbidities [20], including rare diseases [21]. Moreover, NAMs have the potential to incorporate complex mixtures and cumulative exposures [22][23][24]. Probabilistic methods can incorporate variability into predictions and have been used to derive reference dose estimates [25] and points of departure [23].…”
Section: Genomicsmentioning
confidence: 99%
“…Cell-based studies allow for high-throughput testing of both defined [ 10 ] and environmental [ 11 ] mixtures. Analyses of dose reconstruction of mixture effects based on in vitro data have concluded that model-based predictions of mixture effects from the individual components are often under-predictive [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent attempts have been made at investigating the impact of chemical mixtures, the results of which suggest that, although TD variability in response to mixtures appears no greater than that of its most variable component, component-based additivity models tend to underestimate mixture variability. 25 , 26 However, understanding the contributions of nongenetic host factors to variability—which can range widely across epigenetics, life stage, background disease, and nonchemical stressors 27 —remains a largely unmet challenge.…”
mentioning
confidence: 99%